Evolution of Peak Shear Strength of Rock Fractures Under Conditions of Repetitive Dry and Wet Cycling - Guo, Baohua; Cheng, Tan; Sun, Jiehao; Tian, Shixuan; Chen, Yan; Niu, Yongbin (Frontiers in Earth Science, 2022)
In order to study the shear mechanical properties of rock fracture under dry-wet cycle condition, the irregular artificial splitting fractured sandstone specimens were soaked in chemical solutions with pH of 2, 7 and 12 for 3, 6, 9, 12 and 15 dry-wet cycles. Then, the direct shear tests were carried out on rock fractures under the normal stress of 3, 6, 9, 12 and 15 MPa to study the shear mechanical properties of rock fractures by using the RDS-200 rock direct shear apparatus. The results show that the pre-peak shear stiffness and the peak shear strength of sandstone fractures decrease, and the peak shear displacement increases after dry-wet cycle treatment comparing with those non-soaked rock fractures. The pre-peak shear stiffness, peak shear strength, peak shear displacement and residual shear strength of rock fractures decrease on the whole with the increasing dry-wet cycles. Based on Barton formula of peak shear strength for rock fracture, an empirical formula of peak shear strength for irregular rock fractures under dry-wet cycle condition is proposed by introducing a correction parameter which is used to describe the deterioration degree of the rock fracture friction coefficient caused by dry-wet cycles. The newly proposed formula has a good fitting accuracy for the test shear strength data of rock fractures under dry-wet cycle condition, which is helpful to accurately estimate the peak shear strength of rock fractures under dry-wet cycle condition in engineering practice.